Prevalence of asymptomatic cytomegalovirus (CMV) infection in newborns in northeast Florida - Alissa, Rana; Maraqa, Nizar; Williams, Patty D.; Hipp, Jennifer A.; Nath, Sfurti; Torres, Nicole S.; Lee, Tiffany; Matoq, Amr; Rathore, Mobeen (Frontiers in Epidemiology, 2024)
Background Congenital cytomegalovirus (CMV) infection is the leading cause of hearing loss and neurocognitive delay among children. Affected infants may be asymptomatic at birth and even pass their universal hearing screen. Early identification of CMV-infected infants will allow earlier detection, evaluation and management. The prevalence of congenital CMV infection in the developed world varies geographically from 0.6% to 0.7% of all deliveries and certain regions are at higher risk. The prevalence of congenital CMV is unknown for our region. Aim The purpose of this study was to determine the prevalence of CMV infection among the neonatal population at an urban, tertiary hospital in northeast Florida which serves a large population of patients with low socioeconomic status to assess if universal screening program for congenital asymptomatic CMV infection can be determined. Methods The study was submitted and approved by our Institutional Review Board. We tested the urine for CMV infection in 100 asymptomatic newborns (>32 weeks gestational age and >1,750 g weight at the time of delivery) delivered between June 2016 and July 2017. Results Urine CMV was tested on 100 infants. One infant had a positive urine NAAT for CMV, making the prevalence of congenital CMV infection among asymptomatic newborns in our hospitals' population 1%. Conclusion CMV prevalence in our setting of an urban, tertiary hospital is relatively consistent with the national average of all congenital CMV infections. A policy of universal screening for congenital CMV may be necessary.